Light Sheet Microscopy Using FITC-Albumin Followed by Immunohistochemistry of the Same Rehydrated Brains Reveals Ischemic Brain Injury and Early Microvascular Remodeling - Mohamud Yusuf, Ayan; Hagemann, Nina; Schulten, Sarah; Rausch, Olessja; Wagner, Kristina; Hussner, Tanja; Qi, Yachao; Totzeck, Matthias; Kleinschnitz, Christoph; Squire, Anthony; Gunzer, Matthias; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2021)
Until recently, the visualization of cerebral microvessels was hampered by the fact that only short segments of vessels could be evaluated in brain sections by histochemistry. These limitations have been overcome by light sheet microscopy, which allows the 3D analysis of microvasculature in cleared brains. A major limitation of light sheet microscopy is that antibodies do not sufficiently penetrate into cleared brains. We herein describe a technique of reverse clearing and rehydration, which after microvascular network analysis allows brain sectioning and immunohistochemistry employing a broad set of antibodies. Performing light sheet microscopy on brains of mice exposed to intraluminal middle cerebral artery occlusion, we show that in the early phase of microvascular remodeling branching point density was markedly reduced, more strongly than microvascular length. Brain infarcts in light sheet microscopy were sharply demarcated by their autofluorescence signal, closely corresponding to brain infarcts revealed by Nissl staining. Neuronal survival, leukocyte infiltration and astrocytic reactivity could be evaluated by immunohistochemistry in rehydrated brains, as shown in direct comparisons with non-cleared brains. Immunohistochemistry revealed microthrombi in ischemic microvessels that were likely responsible for the marked branching point loss. The balance between microvascular thrombosis and remodeling warrants further studies at later time-points after stroke.